Business in Fragile Environments: Capabilities for Conflict Prevention. (May 2014) - Ganson, Brian
Abstract While normative frameworks proscribing and prescribing company action in conflict‐prone environments grow in number, both the practice‐oriented and more theoretical literature have been relatively silent on the question of whether and how a company's distinctive organizational capabilities contribute to conflict risk mitigation or conflict resolution in fragile contexts. This article links the practical experience of company managers with conflict management theory to posit that organizational capabilities are a crucial explanatory variable for the gap between desired and observed company performance in fragile contexts. It models a management system for conflict prevention with empirical and theoretical referents. The model provides practitioners with useful diagnostic entry points as they work to improve company operations. At the same time, it brings together diverse conflict management perspectives on company operations in fragile environments so that future case data may be ordered and compared and further theoretical propositions developed and tested.